Academic Dropout among Students with Disabilities in Higher Education: A Bibliometric Study - Velez, Wilson Alexander Zambrano; Augusto, Sornoza Zavala Gioryi; Molano, Pedro Gabriel Marcano; Rodríguez, Omar Torres; Chele, Jorge Luis Pozo (Journal of Posthumanism, 2025)
Students with disabilities are more likely to drop out of school due to barriers to participation. The objective was to analyze the scientific output of academic dropouts among students with disabilities in higher education from 2005 to 2025. The bibliometric method, non-experimental and descriptive design was used. The search was conducted in Scopus and WOS with Boolean descriptors and operators. Data were exported in RIS format and imported into COVIDENCE for PRISMA: identification, screening, and inclusion, with eligibility criteria. Bibliometrix and VOSviewer were used. Scientific output has a growth rate of 14.5%, the most prominent author is Morina, the journals are Disability & Society, African Journal of Disability, and Educational Sciences; the affiliation is the University of Seville, and distribution is Spain, the USA, and the United Kingdom. Meanwhile, co-occurrence analysis found five clusters, and co-authorship networks reaffirm Morina's participation.